Aktualisasi Hukum Hindu Dalam Sistem Hukum di Indonesia - I Nyoman Suarna; I Nyoman Sulastra; Ni Ketut Windhi Maretha (Jatiswara, 2015)
The purpose of this study was 1) to determine the form of actualizing the Hindu law in the justice system in Indonesia; 2) To know the steps undertaken by the Judge in the Hindu law actualize in Mataram District Court and 3) to identify the constraints faced by judges in actualizing the Hindu law in Mataram District Court. This research is normatik emperik approach to legislation, the concept and approach historical and descriptive qualitative analysis. Results resecht Form actualization Hindu law in the judicial system in Indonesia in court for a judge to a case relating to a criminal hindu if realition with the use of positive law such as Criminal Code, if the related civil Civil Code only. Actualization of Hindu Law which implied only concern cases of divorce, inheritance, child pengankatan petition refers also to the Hindu law Tri Upasaksi are witnesses to god, witness the human, and witness to the bhuta. Steps taken by the judge in actualization law During this time the judges have never done respending, but judges apply existing law is state law either criminal case along can provide a sense of justice, if not then the judges will do the excavation of Hindu law which live in the community either in Sruti, Menawadharmasastra and Hindu literature.